Multiple action sites of ultrasound on Escherichia coli and Staphylococcus aureus - Xinyu Liao; Jiao Li; Yuanjie Suo; Shiguo Chen; Xingqian Ye; Donghong Liu; Tian Ding (Food Science and Human Wellness)
Ultrasound, is thought to a potential non-thermal sterilization technology in food industry. However, the exact mechanisms underlying microbial inactivation by ultrasound still remain obscure. In this study, the action modes of ultrasound on both Gram-negative and Gram-positive microorganisms were estimated. From colony results, ultrasound acted as an irreversible effect on both Eshcerichia coli and Staphylococcus aureus without sublethal injury. The result in this study also showed that a proportion of bacteria subpopulation suffered from serious damage of intracellular components (e.g. DNA and enzymes) but with intact cell envelopes. We speculated that the inactivated effects of ultrasound on microbes might more than simply completed disruption of cell exteriors. Those microbial cells who had not enter the valid area of ultrasonic cavitation might be injected with free radicals produced by ultrasound and experienced interior injury with intact exterior structure, and others who were in close proximity to the ultrasonic wave field would be immediately and completely disrupted into debris by high power mechanic forces. These findings here try to provide extension for the inactivation mechanisms of ultrasound on microorganisms. Keywords: Ultrasound, Inactivation mechanism, Reactive oxygen species (ROS), Staphylococcus aureus, Escherichia coli